Slow Tourism and Sustainable Tourism: A Study in the Losari Beach Tourism Area, Makassar City - Marshanda Ma'rief Attas; Abdu Rahman; Sri Wahyuni (Politeknik Pariwisata Makassar, 2026)
This study was conducted to analyze and identify the indirect role of the Makassar city government in the concepts of slow tourism and sustainable tourism in the Losari Waterfront Tourism Area. The study aims to identify the challenges in implementing slow tourism and sustainable tourism, followed by outlining effective policy planning strategies to support slow tourism and sustainable tourism in the Losari Waterfront Tourism Area, Makassar City. The methodology used in this study is a qualitative descriptive research method. The data collection techniques for this qualitative research involve the researcher interacting directly through observation, interviews, and literature reviews from journals or related documents. The research results indicate that the Makassar City Government, through the Tourism Office, has indirectly supported the implementation of the slow tourism concept, where the elements of attractions, facilities, and accessibility are already quite good. However, there are still challenges to be overcome if the concept of slow tourism and sustainable tourism is to be officially implemented. Therefore, to implement this concept, a policy roadmap is needed that gradually outlines the implementation of slow tourism in the Losari Beach tourist area, Makassar City.